(untitled) (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
At the beginning of the 21 century it became clear that the «heavenly» cosmic philosophy of Tsiolkovsky and so called the «planetary» cosmic presented by F.A. Tsander are both to some extend premature, and the «earth» or «ground» cosmic philosophy of Yu.V. Kondratyuk is the most urgent for the Earth because it could realize some peaceful space programs for the benefit of mankind. «The whole universe space is developing not in accordance with Tsiolkovsky’s or Tsander’s theories but with that of Kondratyuk», said B.I. Romanenko, the scientist, who has been studying the interplanetary space for many years and who was Yuriy Kondratyuk’s colleague and biographer. In the history of national science it is difficult to find more dramatic fortune than the life and career of the outstanding self-taught scholar from Poltava.